Use of Virtual Reality in Psychiatric Diagnostic Assessments: A Systematic Review - Geraets, Chris N. W.; Wallinius, Märta; Sygel, Kristina (Frontiers in Psychiatry, 2022)
Background: Technological developments such as Virtual reality (VR) provide new opportunities to extend and innovate mental healthcare. VR as a tool for clinical assessment has been described as promising, as it can enable real-time assessment within real-like environments or contexts as opposed to self-report and behavioral tasks in laboratory settings. Objective: With this systematic review we aimed to provide an overview of recent studies using VR in the assessment of psychiatric disorders. Methods: A systematic search was performed using Pubmed, Embase, PsycInfo, and Web of Science between 2016 and 2020. Studies were included if they used immersive VR, concerned assessment of psychiatric symptoms/disorders, and included adult patients with psychiatric disorders. Results: The search resulted in 3163 potentially eligible articles, from which a total of 27 studies fulfilled inclusion criteria. Most studies considered anxiety (n = 7), addictive, (n = 7), or psychotic disorders (n = 5). Regarding ADHD (n = 3), PTSD (n = 3), and pedophilic disorder (n = 1), a few studies had been performed since 2016. The majority of the included studies compared patient groups to healthy control groups. Discussion: Recent studies on VR-assisted psychiatric assessments have been conducted to validate VR environments, to assess symptoms for diagnostics or therapy goals, search for biomarkers, and to gain knowledge on psychiatric disorders. VR tasks were able to detect some difference between patient and healthy control groups, mainly with regard to self-report measures. Despite previous, promising prospects, the use of VR as a tool in clinical assessments must still be considered as a field in need of continued developments and evaluations.